2017
DOI: 10.4018/ijictrame.2017070103
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Mobile Phone Use in Nigerian Agricultural Development

Abstract: This study used 328 smallholder farmer respondents to investigate its objectives of how farmers use mobile phone technology, what benefits they have gained from the use, and the constraints encountered during the process. The quantitative data collected through a process of questionnaire administration were analysed using Stata 12 software. The results indicate that mobile phone usage for farm and other social purposes has increased with farmers. The farmers also spend almost 40% of their phone bills on farm-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…We present the findings based on the three research questions and the outcomes of data analysis. Starting with agricultural uses of mobile phone, the studies reviewed indicated that mobile phones serve as a special conduit to all forms of agricultural information [16,17,18,19]. These range from information on farm inputs to marketing activities.…”
Section: Findings and Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…We present the findings based on the three research questions and the outcomes of data analysis. Starting with agricultural uses of mobile phone, the studies reviewed indicated that mobile phones serve as a special conduit to all forms of agricultural information [16,17,18,19]. These range from information on farm inputs to marketing activities.…”
Section: Findings and Analysismentioning
confidence: 99%
“…Level of education: Possessing a formal education has been noted as a contributory factor to mobile phone use [20,21,16,17,22,19]. This is because educated farmers are able to read and most mobile phone features are written in English.…”
Section: Findings and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The growth in ICT creates avenues for African farmers to upgrade their knowledge and livelihoods [14], [15]. According to the work carried out by [16], the level of usage of mobile phone, its usefulness and challenges was examined among the farmers in some rural part of Africa: At the end of this study, it was found out that 40% of farmers' phone bills were spent on farm activities while 17. 32% were spent on gaining more knowledge and marketing farm produce.…”
Section: Information and Communication Technology In Agriculturementioning
confidence: 99%